2006
DOI: 10.1177/0091270005284853
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of Lopinavir/Ritonavir in HIV/Hepatitis C Virus–Coinfected Subjects With Hepatic Impairment

Abstract: The effect of hepatic impairment on lopinavir/ritonavir pharmacokinetics was investigated. Twenty-four HIV-1-infected subjects received lopinavir 400 mg/ritonavir 100 mg twice daily prior to and during the study: 6 each with mild or moderate hepatic impairment (and hepatitis C virus coinfected) and 12 with normal hepatic function. Mild and moderate hepatic impairment showed similar effects on lopinavir pharmacokinetics. When the 2 hepatic impairment groups were combined, lopinavir Cmax and AUC12 were increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
22
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 9 publications
5
22
0
1
Order By: Relevance
“…This observation was based on the measurement of plasma levels of LPV and ATV and comparisons made between patients with and without cirrhosis. A recent multiple-dose study found that the C min of LPV was higher in HIV-infected patients with chronic hepatitis than in control subjects [23]. However, in accordance with our findings, no significant differences in LPV plasma levels were seen in the group of patients with liver disease when patients with cirrhosis were compared with those with mild hepatic impairment.…”
Section: Discussionsupporting
confidence: 90%
“…This observation was based on the measurement of plasma levels of LPV and ATV and comparisons made between patients with and without cirrhosis. A recent multiple-dose study found that the C min of LPV was higher in HIV-infected patients with chronic hepatitis than in control subjects [23]. However, in accordance with our findings, no significant differences in LPV plasma levels were seen in the group of patients with liver disease when patients with cirrhosis were compared with those with mild hepatic impairment.…”
Section: Discussionsupporting
confidence: 90%
“…For example, for subjects with moderate hepatic impairment, amprenavir AUC (0-) values increased 51 to 70% in the ritonavir-boosted setting versus 2.5-fold in the unboosted amprenavir study; similarly, for subjects with severe hepatic impairment, amprenavir AUC (0-) values increased 80% in the ritonavirboosted setting versus 4.5-fold in the unboosted amprenavir study. Ritonavir exposure [AUC (0-) ] also increased 93 to 120% for subjects with moderate hepatic impairment and 180% for subjects with severe hepatic impairment, and the increases were of a magnitude similar to those reported for lopinavir/ritionavir (3).…”
Section: Discussionsupporting
confidence: 71%
“…Our data are in agreement with those of other studies reporting that hepatic impairment does alter the pharmacokinetics of ATV. 13,24 In our patients, the 400 mg OD unboosted regimen in HIV+/HCV-negative subjects provided significantly lower ATV trough concentrations than did the standard dosage of 300ATV + 100RTV OD (median 0.23 versus 0.85 mg/mL; P , 0.0001). The same difference between the 2 ATV regimens was also confirmed in HIV+/HCV-positive patients (0.52 mg/mL for the 400 OD and 0.96 mg/mL for the 300/100 OD, respectively).…”
Section: Discussionmentioning
confidence: 59%
“…Results from other studies support the concept that the intrinsic clearance of PIs in patients with liver disease is only partially affected after being inhibited by low-dose RTV coadministration, because no significant changes in drug pharmacokinetics in mild liver dysfunction with morphologic evidence of cirrhosis were observed. [23][24][25][26][27] This PK study has some limitations. First of all, it was based on a retrospective observational TDM data set and not on a controlled protocol.…”
Section: Discussionmentioning
confidence: 99%